The man who invented fiction : how Cervantes ushered in the modern world - Egginton, William, 1969- (Bloomsbury USA, 2016)
"In the early seventeenth century, a crippled, graying, almost toothless veteran of Spain's wars against the Ottoman Empire published a book. It was the story of a poor nobleman, his brain addled from reading too many books of chivalry, who deludes himself that he is a knight errant and sets off on hilarious adventures. That book, Don Quixote, went on to sell more copies than any other book beside the Bible, making its author, Miguel de Cervantes, the single most-read author in human history. Cervantes did more than just publish a bestseller, though. He invented a way of writing. This book is about how Cervantes came to create what we now call fiction, and how fiction changed the world."--